Foreign Body Reaction with High Standard Uptake Value Level in 18-FDG PET/CT Mimicking Relapse in an 8-Year-Old Patient Diagnosed with Hodgkin Lymphoma: A Case Report - Erdoğan, Derya; Bozkurt, Ceyhun; Özmen, Özlem; Boduroglu, Esin; Sahin, Gürses (European Journal of Pediatric Surgery Reports, 2013)
Combined positron emission tomography and computed tomography (PET/CT) using 18-fluorodeoxyglucose (18-FDG) is one of the most effective methods to identify pathological lymph node involvement. We report the case of a child who underwent cervical lymph node biopsy and chemotherapy for Hodgkin disease. Three years after surgery, PET/CT identified an intense localization of 18-FDG in the inferior cervical region. This finding led to a reexcision of the mass. The only finding was a granuloma arising in reaction to a hemostatic sponge.
Keywords: positron emission tomography; foreign body; Hodgkin lymphoma; lymph node; childhood